PENGARUH PRODUK DOMESTIK BRUTO (PDB), PENGANGGURAN, DAN KEMISKINAN TERHADAP ISLAMIC HUMAN DEVELOPMENT INDEX (I-HDI) DI INDONESIA - Rifki Nanda putra Lubis; Imsar Imsar; Atika Atika (ITB AAS Indonesia Surakarta, 2024)
Unemployment and poverty are economic problems that are mostly faced by developing countries. Increasing unemployment and poverty will have a negative impact on Gross Domestic Product (GDP) which will then have an impact on human development in the country. The Human Development Index (HDI) is considered unable to reflect the religious and ethical perspective of socio-economic development in countries where the majority of the population is Muslim such as Indonesia. Therefore, the IHDI (Islamic Human Development Index) was created, a measurement based on the five dimensions of Maqasid Al-Shari'ah. This research aims to determine the influence of Gross Domestic Product, unemployment and poverty on the Islamic Human Development Index in Indonesia in 2015-2021. The data used in this research is secondary data obtained from publications by the Central Statistics Agency (BPS). This research is quantitative research using multiple linear regression methods. The research results show that GDP has a positive and insignificant influence on IHDI. Meanwhile, the unemployment variable has a negative and insignificant influence on IHDI. And the poverty variable has a negative and significant influence on IHDI. Simultaneously, Gross Domestic Product, Unemployment and Poverty have a significant effect on IHDI. The results of this research can provide insight to policy makers (government) about the importance of paying attention to factors such as GDP, unemployment and poverty in an effort to increase the level of human development. such as stimulating economic growth, reducing unemployment levels, as well as economic empowerment programs to overcome poverty.